Analysis of Antalgin (Metamizole Sodium) in Generic Tablet Preparations Using Ultraviolet Spectrophotometry - Sulasmi, Sulasmi; Syarifudin, Aminah (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2023)
Antalgin (metamizole sodium) is a non-steroidal anti-inflammatory analgesic widely used in pain management. Quantitative determination of antalgin in pharmaceutical preparations is essential to ensure patient safety and drug quality. This study aimed to determine the maximum absorption wavelength, establish a calibration curve, and quantify antalgin content in generic tablet preparations using ultraviolet (UV) spectrophotometry. Standard solutions were prepared in 0.1 N HCl at concentrations of 8, 12, 16, 20, and 24 μg/mL. The maximum absorption wavelength was determined at 255 nm. The calibration curve yielded a linear regression equation of y = 0.0271x + 0.0031 with a correlation coefficient r = 0.9994, satisfying the acceptance criterion of r ≥ 0.995. Quantitative analysis of six replicate samples yielded a mean antalgin content of 82.78% (range: 77.55–88.00%), which did not meet the Indonesian Pharmacopoeia VI requirement of 95.0–105.0%. The substandard content may be attributed to excipient interference, procedural errors, and improper storage conditions. UV spectrophotometry demonstrated acceptable linearity and precision for antalgin determination.